Răspuns :
Aducem ambele fractii din paranteza la acelasi numitor (adica 18). Asa ca, [tex] \frac{2}{3} [/tex] × ([tex] \frac{45}{8} [/tex] + [tex] \frac{10}{18} [/tex] ) ×[tex] \frac{3}{4} [/tex] = [tex] \frac{2}{3} × \frac{55}{18} × \frac{3}{4} [/tex] = [tex] \frac{1}{3} × \frac{x55}{9} × \frac{3}{4} [/tex] = [tex] \frac{55}{36} [/tex]
2/3 x ( 5·9 / 18 - 5·2 /18 ) : 4/3
= 2/3 x ( 45/ 18 - 10/18) : 4/3
= 2/3 x 35/18 : 4/3
= ( 2·35) / 3·18 : 4/3
= 35/27 x 3/4
= 35/36
= 2/3 x ( 45/ 18 - 10/18) : 4/3
= 2/3 x 35/18 : 4/3
= ( 2·35) / 3·18 : 4/3
= 35/27 x 3/4
= 35/36